Estudio de factibilidad para la creación de una heladería artesanal tipo tailandesa con frutas orgánicas exóticas de Colombia en la ciudad de Bogotá, D.C. (2018)
The present feasibility study for the creation of a Thai artisanal ice cream shop with exotic organic fruits from Colombia in the city of Bogotá, DC It is possible thanks to the opportunities in the ice cream sub sector and industry, and in the change of habit of the capitals of healthier products, which do not contain chemicals, preservatives and artificial colors. A market study was carried out, in which a real demand was investigated for organic doctors, in order to find and develop strategies to attract and retain future clients. It is about the capacity of the ice cream shop based on the demand, the suppliers are selected, as the machinery and the equipment are provided to the client an ice cream of exquisite flavor and quality. The ice cream facilities were designed with respect to the point of sale that has opted for the development of the project, with their respective signs of safety and health at work. Strategic planning, human talent management and the salary study were carried out for the administration of the project, as well as to analyze the legal aspects that should be taken into account at the time of the constitution of the company. Finally, a financial study was carried out to determine the viability of the project.